From African languages to an African perspective on language: The work and research of Prof. Marianna W. Visser - Andrason, Alexander (Stellenbosch Papers in Linguistics Plus, 2019)
This paper discusses the contribution of Prof. Marianna W. Visser to African linguistics. I present the academic and professional trajectory of Prof. Visser and her research achievements, focusing on publications in three branches of language science: formal linguistics (morpho-syntax and semantics), applied linguistics (language policy and multilingual education), and text-linguistics (appraisal theory and discourse analysis). These three areas and their respective themes are subsequently reflected in the selection of articles included in the volume, which this article also introduces.